Gamified dances, digital and socio-emotional skills in collaborative virtual environments of university students surviving the Covid-19 virus - Holguin-Alvarez, Jhon; Cruz-Montero, Juana (Frontiers in Education, 2023)
The use of virtual dance avatars and virtual learning guides has enabled gamified dance teaching to virtualize the current university. In this experience, the objective was to test four hypotheses about the gamified dance developed in collaborative Zoom environments, and its effects on the digital and socioemotional skills of individuals who were severely or moderately infected by the Covid-19 virus between the years 2020 and 2022. We worked with 119 students and eight teachers from the Professional School of Primary Education of a private university in the city of Lima (Peru). An experimental design with pre and post-test was applied and Likert-type scales were used for data collection. The experience with gamified dances took place over four weeks in a dance competition at the university. The results allow us to assert that gamified dances developed digital skills, emotional skills, as well as socioemotional skills. These skills differ between the experimental group and the control group, with the exception of digital security skills, and the ability to improve self-esteem, which are skills that require more body practice as was achieved in the experimental group (dance virtual), which was also developed in the students of the control group (face-to-face dance).